2021
DOI: 10.1063/5.0039918
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic signature of negative electronic compressibility from the Ti core-level of titanium carbonitride MXene

Abstract: Two-dimensional transition metal carbides, carbonitrides, and nitrides, called MXenes, exhibit high metallic conductivity, ion intercalation capability, and reversible redox activity, prompting their applications in energy storage and conversion, electromagnetic interference (EMI) shielding, and electronics, among many other fields. It has been shown that replacement of ∼50% of carbon atoms in the most popular MXene family member, titanium carbide (Ti3C2Tx), by nitrogen atoms, forming titanium carbonitride (Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Carbonitride MXenes prepared through this method have been used in sensing, energy storage, and biomedical applications. [56][57][58][59] 3.1.3 KF-HCl etching method. Liang and co-workers reported the synthesis of Ti 2 C 0.5 N 0.5 T x MXene from its MAX phase Ti 2 AlC 0.5 N 0.5 using the KF-HCl (in situ HF) etching approach similar to that of the LiF-HCl mild etching method.…”
Section: Carbonitride Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonitride MXenes prepared through this method have been used in sensing, energy storage, and biomedical applications. [56][57][58][59] 3.1.3 KF-HCl etching method. Liang and co-workers reported the synthesis of Ti 2 C 0.5 N 0.5 T x MXene from its MAX phase Ti 2 AlC 0.5 N 0.5 using the KF-HCl (in situ HF) etching approach similar to that of the LiF-HCl mild etching method.…”
Section: Carbonitride Mxenesmentioning
confidence: 99%
“…The carbonitride MXene Ti 3 CN shows remarkable EMI shielding effectiveness (SE), superb charge storage capacity, high negative charge in solution, excellent stability, and good optical and transport properties. 58,60 The exact role of nitrogen atoms and their inuence on the properties of the carbonitride MXene are yet to be explored and understood. However, a few reports have elucidated the origin of properties of carbonitride MXenes through experimental and theoretical studies.…”
Section: Propertiesmentioning
confidence: 99%
“…Recent experimental studies have revealed some unique properties of Ti 3 CNT x , such as a higher EMI shielding effect, superior charge storage capacity, 13,14 and more negative surface charge than Ti 3 C 2 T x MXenes. 15 In addition, it is speculated that the additional Ti-N bond in Ti 3 CNT x has a signicant effect on the charge storage capacity. 15 Therefore, Ti 3 CNT x MXene is an excellent candidate for the electrode material of supercapacitors, and it is a signicant study to construct twodimensional capacitive materials with Ti 3 CNT x MXenes.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition, it is speculated that the additional Ti-N bond in Ti 3 CNT x has a signicant effect on the charge storage capacity. 15 Therefore, Ti 3 CNT x MXene is an excellent candidate for the electrode material of supercapacitors, and it is a signicant study to construct twodimensional capacitive materials with Ti 3 CNT x MXenes. Ti 3 CNT x nanosheets also suffer from severe restacking like other MXenes, thereby reducing the accessibility of 2D nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The general chemical formular for MXenes is M n + 1 X n T x (n = 1-4). Specifically, M stands for early transition metals (including Ti, [7] V, [8] Nb, [9] Mo, [10] etc. ); X represents C and/or N; T x refers to surface terminating groups (e. g., =O, À OH, and À F).…”
Section: Introductionmentioning
confidence: 99%